Characterization of high photosensitivity nanostructured 4H-SiC/p-Si heterostructure prepared by laser ablation of silicon in ethanol. (September 2017) - Ismail, Raid A.; Khashan, Khawla S.; Mahdi, Rana O.
Abstract: This paper presents the first study on characterization of high sensitivity 4H-SiC/Si heterojunction photodetector prepared by deposition of SiC nanoparticles NPs on silicon substrate by drop casting. Synthesis of the SiC NPs was performed by laser ablation of silicon target immersed in ethanol with 1.064 µm Nd:YAG laser pulses at various laser fluences (318-9.55) J/cm 2 . The morphological, structural, electrical, and optical properties of SiC NPs were investigated as function of laser fluence. The absorption data showed that the value of optical energy gap of SiC nanoparticles depend on the laser fluence. TEM investigation showed that SiC NPs having spherical shape with sizes in the range (5–65) nm. The optical energy gap of SiC NPs prepared at different laser fluences has been determined from optical properties and found to be in the range (3.45–3.75 eV). The electrical properties of SiC/Si heterojunction shows a good rectification ratio and the value of ideality factor varied from 1.72 to 3.51 depending on the laser fluence. Capacitance –voltage properties of heterojunctions showed a linear relationship between C −2 and reverse bias voltage and the value of built-in potential was found in the range (0.45–0.8) V. The effect of laser fluence on the photodetector figures of merit namely; photosensitivity, detectivity and rise time was discussed and analyzed.